Effect of cell-conditioned media on biomass production of Leishmania parasites - Bagirova, Melahat; Koc, Rabia Cakir; Allahverdiyev, Adil; Ersoz, Malice (Tubitak Scientific & Technological Research Council Turkey, 2012)
A large amount of parasite biomass production necessitates a higher volume of culture media, and this further increases the overall cost. For this reason, novel and alternative culture supplementary materials have been continuously investigated. The aim of this study was therefore to evaluate the effect of cell-conditioned media, collected as waste material during routine cell culture, on the growth and development of Leishmania parasites in vitro. In this study, for the first time, we show that cell-conditioned medium obtained from MCF-7 culture increased the growth of Leishmania parasites in vitro. These results show that the metabolites that are present in cell-conditioned media may play an important role in in vitro parasite culture. Cell-conditioned media may be used as an economic tool for isolation, cultivation, and obtaining biomass of Leishmania parasites in laboratory conditions.
Keywords: Culture; medium; Leishmania; large-scale; biomass; FETAL BOVINE SERUM; DEFINED MEDIUM; INVITRO CULTIVATION; PROMASTIGOTES; SENSITIVITY; DONOVANI; Life Sciences & Biomedicine - Other Topics